REVITALIZING DRIVE: UNVEILING MOTIVATIONAL FACTORS FOR FOOD DELIVERY WORKERS - Natarajan, Visweswaran Ramesh; Y, Benazir (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study aims to explore the complex web of motivational factors that influence the performance and job satisfaction of food delivery workers. By delving into the dynamics of motivation within this unique work context, we can better understand what drives these workers. Motivation plays a crucial role in shaping the outcomes of businesses, both quantitatively and qualitatively. Extensive research worldwide highlights the importance of motivation, as its absence can have negative consequences. While external motivation can encourage employees, true inspiration comes from within. Regardless of employees' backgrounds, education, or work experiences, their core aspirations revolve around fulfilling personal needs, ambitions, desires, and goals. These aspirations are connected to survival, security, a sense of belonging, positive self-perception, and self-fulfillment. The abstract captures the essence of the study, emphasizing its focus on understanding the intricate motivational factors that impact food delivery workers' performance and job satisfaction.